1984
DOI: 10.1128/mcb.4.9.1718
|View full text |Cite
|
Sign up to set email alerts
|

Effects of epidermal growth factor and 12-O-tetradecanoylphorbol-13-acetate on metabolism of the epidermal growth factor receptor in normal human fibroblasts.

Abstract: The biosynthesis, phosphorylation, and degradation of the epidermal growth factor (EGF) receptor were examined in normal human fibroblasts. The receptor was initially synthesized as an Mr = 160,000 immature form which matured to an Mr = 170,000 form in a monensin-sensitive manner. Tunicamycin treatment led to the accumulation of an Mr = 130,000 protein. The receptor was phosphorylated on serine and threonine residues in normally growing and quiescent cells, and treatment with EGF or the tumor promoter 12-0-tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
38
0

Year Published

1985
1985
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(41 citation statements)
references
References 31 publications
3
38
0
Order By: Relevance
“…Phosphate labeling of the EGF receptor at serine and threonine increases by about 100%, but phosphate labeling at tyrosine increases by at least 300% (17). Tyrosine phosphorylation of EGF receptors in EGFtreated fibroblasts has also been detected (9). Most of the phosphotyrosine is found at a single position in the EGF receptor, now identified as tyrosine 1173 (10).…”
mentioning
confidence: 97%
“…Phosphate labeling of the EGF receptor at serine and threonine increases by about 100%, but phosphate labeling at tyrosine increases by at least 300% (17). Tyrosine phosphorylation of EGF receptors in EGFtreated fibroblasts has also been detected (9). Most of the phosphotyrosine is found at a single position in the EGF receptor, now identified as tyrosine 1173 (10).…”
mentioning
confidence: 97%
“…Several PKC isoforms physically interact with tyrosine kinase receptors, including epidermal growth factor (EGF) (Chen et al, 1996), insulin-like growth factor-I (IGF-I) (Li et al, 1998) and insulin (Formisano et al, 1998;Caruso et al, 2001;Oriente et al, 2001) receptors. In turn, PKC-mediated serine/threonine phosphorylation has been shown to inhibit EGFR (Decker, 1984;Downward et al, 1984;Chen et al, 1996), insulin receptor (Takayama et al, 1984;Caruso et al, 2001), and hepatocyte growth factor receptor (Met) (Gandino et al, 1994) by attenuating their intrinsic tyrosine-kinase enzymatic activity and their autophosphorylation on tyrosine.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of ligand-induced receptor internalisation in normal and cancer cells, and in perfused rat liver, showed that endocytosis is followed by proteolysis of receptor predominantly in the lysosomes, with half-life depending on cell type (Beguinot et al, 1984;Stoscheck and Carpenter, 1984a,b;Dunn et al, 1986;Gamou and Shimizu, 1987;Sunada et al, 1990). Endocytosis and degradation were originally proposed to provide a mechanism for the generation of a non-membrane-bound second messenger, communicating cell membrane events to the nucleus (Das and Fox, 1978;Decker, 1984;Cohen and Fava, 1985;Kay et al, 1986). However, internalisation-defective EGF receptor transfectants have been shown to respond to mitogenic stimulation by EGF, suggesting that receptor degradation is not an obligatory step in signal transduction (Wells et al, 1990).…”
mentioning
confidence: 99%